Digger Seasamia larval stage (Lepidoptera: Noctuidea) reared on artificial diet - Juhayna Ali (College of Education for Pure Sciences, 2005)
Seasmia cretlca (Led.) was reared on lour types of artificial diet Ivariluoto. 1078 ; Szumkowski , 1978 ; Infant food (Hilal), 1983 and Smirnoff; 1 985 for two gcneratioi at 3 different temperatures. The generation period ranged between 39-43 day. The highest average number ol'eggs per female was 958.800, morlaiity wa mainin ll. -al stage, and reached a high as 84.80% at 30°C vhen reared on 2nd artificial diet.